ARM MUSCLES EXPLOSIVE POWER TO INCREASE DISCUS THROW SKILL - Miskalena, M.; Tangkudung, James A.P. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The purpose of the study is to find out the relationship among arm muscles explosive power, body core flexibility, achievement motivation and discus throw skill. In this case, the samples totaled 50 students from study program of physical education, faculty of pedagogy and science education "Syiah Kuala" University involving 100 (male) students selected by simple random sampling technique. This research using survey method, quantitative approach and correlational technique. The research concludes (1) it has positive relationship between arm power explosive power and discus throw skill (2) it has relationship significantly between body core flexibility and discus throw skill. (3) The relationship is positive between motivation and discus throw skill, (4) it has positive relationship among arm muscles explosive power, achievement motivation and discus throw skill.